Pengembangan e-Jobsheet Berbantu Tinkercad Kelas XI pada Mata Pelajaran Sistem Kendali Elektronik di SMK Negeri 4 Pariaman - Arizqa, Tifani Putri; Asmara, Delvi (TSAQOFAH, 2026)
This study was motivated by the limited availability of practical learning media and the low level of student engagement in learning Electronic Control Systems at vocational high schools, where the use of conventional media makes it difficult for students to understand application-oriented concepts that require concrete visualization of circuits. The study aimed to develop an E-Jobsheet learning media assisted by Tinkercad for the Electronic Control Systems subject in eleventh-grade classes at SMK Negeri 4 Pariaman to support more interactive and flexible practicum activities. A Research and Development (R&D) method was employed using the 4D model, which comprises the define, design, development, and disseminate stages. The trial subjects consisted of 20 students from class XI Industrial Electronics Engineering. The research instruments included material expert validation sheets, media expert validation sheets, and student practicality questionnaires, while the data were analyzed using quantitative descriptive techniques to determine the feasibility level of the developed learning media. The results showed that the media developed fell into the very valid category, with material expert validation of 83.60% and media expert validation of 83%, as well as a practicality test result of 89.15% in the very practical category. The study concludes that the Tinkercad-assisted E-Jobsheet is suitable for use as practicum learning media and has the potential to enhance students’ interest, engagement, and understanding in learning Electronic Control Systems at vocational high schools.